Respuesta :
2^2 = 4
answer starts with 4
(xy7)^2 = x^2 y(7*2) = x^2y^14
(y^4)^3 = y^(4*3) = y^12
answer is 4x^2 y^14*y^12
= 4x^2 y^(12+14)
= 4x^2y^26
D
answer starts with 4
(xy7)^2 = x^2 y(7*2) = x^2y^14
(y^4)^3 = y^(4*3) = y^12
answer is 4x^2 y^14*y^12
= 4x^2 y^(12+14)
= 4x^2y^26
D
Answer:
The given expression [tex]\left(2xy^7\right)^2\left(y^4\right)^3[/tex] is simplified to [tex]4x^2y^{26}[/tex]
Step-by-step explanation:
Given : Expression [tex]\left(2xy^7\right)^2\left(y^4\right)^3[/tex]
We have to write the correct simplification for the given expression [tex]\left(2xy^7\right)^2\left(y^4\right)^3[/tex]
Consider the given expression [tex]\left(2xy^7\right)^2\left(y^4\right)^3[/tex]
Apply exponent rule, [tex]\left(a\cdot \:b\right)^n=a^nb^n[/tex]
We have,
[tex]=2^2x^2\left(y^7\right)^2[/tex]
Simplify, we have,
[tex]=2^2x^2y^{14}[/tex]
Apply exponent rule, [tex]\left(a^b\right)^c=a^{bc}[/tex]
Simplify, we have,
[tex]=y^{4\cdot \:3}=y^{12}[/tex]
Thus, The expression becomes, [tex]=2^2x^2y^{14}y^{12}[/tex]
Apply exponent rule, [tex]\:a^b\cdot \:a^c=a^{b+c}[/tex]
[tex]y^{14}y^{12}=\:y^{14+12}=\:y^{26}[/tex]
Simplify, we have,
[tex]=4x^2y^{26}[/tex]
Thus, The given expression [tex]\left(2xy^7\right)^2\left(y^4\right)^3[/tex] is simplified to [tex]4x^2y^{26}[/tex]